Efeito da exposição crônica do extrato aquoso de Ilex paraguariensis sobre o comportamento e o perfil lipídico em Caenorhabditis elegans - Machado, Marina Lopes (2016)
Ilex paraguariensis, is a plant widely consumed in southern Brazil, Uruguay and Argentina, and well characterized for its antioxidant and stimulating properties, and could be used as modulator of fat storage in order to control obesity, a worldwide problem. Thus, the effect of chronic consumption of I. paraguariensis on fat metabolism was investigated using the nematode Caenorhabditis elegans. First was carried out the identification and quantification, by HPLC-DAD, of Ilex paraguariensis aqueous extract constituents, later, the nematodes were treated with 1 mg/ml of I. paraguariensis from L1-larvae-stage until adulthood. The extract concentration was chosen because exhibited antioxidant proprieties against juglone, a generator of reactive oxygen species, since these are elevated in fat tissue of obese people. Lipid accumulation, total body energy expenditure and behavioral parameters were analyzed. Ilex paraguariensis decreased BODIPY labeling by 63.36% compared to control without affecting behaviors related to energetic balance. Total body energy expenditure of N2 wild-type, nhr-49 and ador-1 knockout strains was performed through oxygen consumption, Ilex paraguariensis was able to increase oxygen consumption only in N2 worms. In conclusion, Ilex paraguariensis decreased fat deposits and increased consumption of oxygen in N2 worms dependent on NHR-49 and ADOR-1 pathways.